The Skills of High School Mathematic Teachers in Utilizing the Merdeka Belajar Plafform - I Wayan Sumandya; I Wayan Widana; I Nyoman Bagus Suweta Nugraha (Indonesian Research Journal in Education |IRJE|, 2022)
Post-pandemic education recovery begins with breakthroughs according to changing times and technology. Educators are required to be more creative and innovative and carry out learning appropriate to the characteristics of students. This research was to determine the skills of mathematics teachers in utilizing the Merdeka Mengajar platform and how the quality of mathematics learning. The researchers used mixed method research, which combined quantitative and qualitative methods. The population in this research consisted of 135 people, with a total of 27 schools (16 private schools and 11 public schools). This research used the cluster random sampling technique with a sample of 36 teachers from 12 schools (6 private and 6 public schools). The research results showed that the mathematics teacher's skills in utilizing the Merdeka Mengajar platform were in the "not good" category. The quality of learning did not increase, and more students obtained learning outcomes under the KKTP (Criteria for Completeness of Learning Objectives).